City Program Implementation Without Slummers in Sinjai District - Syamsuddin Syam; M Erwin Syukri (Jurnal Ad'ministrare, 2020)
In planning and implementation, the public still lacks confidence in the implementation of a city program without slums. This study aims to determine the implementation of a city program without slums. The city program without slums will address slums by building form collaborative through increasing the role of local government and community participation. The research method used is descriptive qualitative. This research uses a phenomenological approach. Data collection is obtained through direct observation of the object of research and in-depth interviews with relevant sources, namely the Spatial Planning and Settlement Service, which is the implementing elements of the Kotaku program led by the head of the Department, as well as partners and communities who are directly involved and feel. And the data analysis technique in this study uses the Mile and Huberman model which suggests that data analysis in qualitative research is carried out interactively and continuously and until it is complete so that the data is saturated. Activities in data analysis are data reduction, data display, conclusion, and verification. The results of this study indicate that the implementation of the Slumless City Program in Sinjai Regency, for the planning stage has not been carried out properly due to the low awareness of the community in attending meetings or deliberations and the lack of socialization carried out by the organizers, in the implementation stage of the KOTAKU program in Sinjai Regency can It is said to be going well because for three years the implementation of the development of the KOTAKU program was able to reduce the location of the slum to 22.59 Herkatar and community participation in the implementation activities was more enthusiastic in providing energy with direct participation compared to the planning stage.